Factors Leading to Staff Turnover - Adilov B. B.; Shodiev T. O. (Researchparks Publishing, 2022)
The article allows you to see the urgency of this problem, its level, for many enterprises, the analysis of staff underestimation in the workplace to identify the causes of employee dissatisfaction and ways to overcome shortcomings in the workplace. The developed practical recommendations not only allow enterprises to reduce the level of employee dissatisfaction and conduct continuous monitoring, but also show ways to improve labor productivity, improve work and product quality, strengthen employee motivation for work and improve the organization labor protection system.